Lugdunin amplifies innate immune responses in the skin in synergy with host- and microbiota-derived factors - Bitschar, Katharina; Kurschus, Florian; Krismer, Bernhard; Peschel, Andreas; Schittek, Birgit (Nature Communications)
Recently our groups discovered lugdunin, a new cyclic peptide antibiotic that inhibits Staphylococcus aureus epithelial colonization in humans and rodents. In this work, we analyzed its immuno-modulatory and antimicrobial potential as a single agent or in combination with other microbiota- or host-derived factors. We show that pretreatment of primary human keratinocytes or mouse skin with lugdunin in combination with microbiota-derived factors results in a significant reduction of S. aureus colonization. Moreover, lugdunin increases expression and release of LL-37 and CXCL8/MIP-2 in human keratinocytes and mouse skin, and results in the recruitment of monocytes and neutrophils in vivo, both by a TLR/MyD88-dependent mechanism. Interestingly, S. aureus elimination by lugdunin is additionally achieved by synergistic antimicrobial activity with LL-37 and dermcidin-derived peptides. In summary, our results indicate that lugdunin provides multi-level protection against S. aureus and may thus become a promising treatment option for S. aureus skin infections in the future., Lugdunin is a peptide antibiotic produced by the skin commensal Staphylococcus lugdunensis. Here, the authors show that lugdunin reduces Staphylococcus aureus colonization in human keratinocytes and mouse skin by inducing the expression of human LL-37 and recruitment of monocytes and neutrophils.